A comparative study of election laws with respect to compulsory voting in the European Union, lessons for Latvia - Ēlerts, Krišs (Riga Graduate School of Law, 2020)
Taking into account the negative trends of voter turnout in the EU during the last decades, the compulsory voting system is widely discussed among researchers and practitioners. However, in Latvia, where the voter turnout is one of the lowest in the EU, the discussion on implementation of compulsory voting in the Latvian electoral system had been initiated but not widely discussed. The objective of the thesis is to conduct a comparative study of election laws with respect compulsory voting in the European Union, analysing the constitutionality of compulsory voting in Latvia. In this thesis, the theoretical and legal aspects of compulsory voting system in the EU are covered. In addition, the comparative study respect compulsory voting system is conducted, as well as the analysis of the voting turnout trends in the EU is provided. Also, the impact of the compulsory voting system has been examined. In case of Latvia, legal analysis of parliamentary election system and the results of the parliamentary system is conducted. Finally, the constitutionality of the compulsory voting system in Latvia is analysed, providing the recommendations on increasing voter turnout and Latvian election regulations.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Election law; Latvia